The Podocyte Power-Plant Disaster and Its Contribution to Glomerulopathy - Müller-Deile, Janina; Schiffer, Mario (Frontiers in Endocrinology, 2014)
Proper podocyte function within the glomerulus demands a high and continuous energy supply that is mainly derived from the respiratory chain of the inner mitochondrial membrane. Dysregulations in the metabolic homoeostasis of podocytes may result in podocyte damage and glomerular disease. This article highlights the current knowledge about podocyte energy supply by the respiratory chain. We review the regulation of mitochondrial oxidative metabolism with regard to podocytopathy and discuss the latest understanding of different mitochondrial dysfunctions of the podocyte in diabetic nephropathy and focal segmental glomerulosclerosis (FSGS). We discuss genetic forms of mitochondriopathy of the podocyte and end with recent knowledge about crosstalk between NADH and NADPH and potential therapeutic options for podocyte mitochondriopathy. We aim to raise awareness for the complex and interesting mechanisms of podocyte damage by impaired energy supply that, despite of novel findings in recent years, is poorly understood so far.